Dialektika Tafsir dan Kemajuan Pengetahuan Sidik Jari dalam Al-Qur’an: Aplikasi Tafsir Kontekstual Abdullah Saeed - Nurmansyah, Ihsan; Dana, Nur Rahma (UIN Sultan Syarif Kasim Riau, 2024)
This paper discusses the contextualization of fingerprints in the Qur'an, specifically in Surah Al-Anfal, verse 12, and Surah Al-Qiyamah, verse 4. Each person's fingerprints are unique, even among identical twins, and they remain unchanged over time, unlike other organs that may change. The aim of this study is to examine how scholars have interpreted the reference to fingerprints in the Qur'an across different eras and how the concept of fingerprints indicated in the Qur'an can be applied in the contemporary context. The analysis employs Abdullah Saeed's contextual approach. The research concludes that: first, linguistically, the term